BUSINESS AND APPLICATION LAYER VIEW: INTEGRATING WAREHOUSE MANAGEMENT SYSTEM WITH ERP FOR OPTIMIZING RETAIL INDUSTRY EFFICIENCY - Ng, Hengky; Dazki, Erick (Jurnal Teknik Informatika (Jutif), 2024)
In the era of globalization and increasingly fierce competition, operational efficiency has become a top priority for the retail industry to meet the growing demands of customers. This journal discusses the importance of WMS (Warehouse Management System) in the retail industry, particularly the benefits of its integration with ERP (Enterprise Resource Planning) systems. The integration process between WMS and ERP will be explained from the perspectives of Business Architecture, Application Architecture, Data Architecture, and Technology Architecture. The main benefits of integrating WMS with ERP include enhanced operational efficiency, reduced inventory costs, faster order fulfillment, and increased customer satisfaction. Thus, this integration enables the retail industry to achieve higher levels of accuracy and responsiveness in supply chain management, helping them stay competitive in an ever-changing market.